The new urban leaders - Ladner, Joyce A. (Washington, D.C. : Brookings Institution Press, 2001)
Publisher Fact Sheet Some of today's best urban leaders don't work for the government--they can be found in nonprofit organizations that serve the working class & poor populations. Based on interviews conducted in major cities including Atlanta, Chicago, Houston, San Francisco, Washington D.C., & New York, this study focuses on exceptional leaders who have developed effective solutions to the complex problems of our inner cities, including education, economic development, & community safety. The New Urban Leadership investigates how & why expert problem solvers chose their career paths, what qualities make them especially successful in their work, & the methods they use to train the next generation of urban leaders.
Annotation Ladner (governmental studies, Brookings Institution) profiles the leaders of the third wave of the civil rights movement and presents case studies explaining the successes of the cooperative programs of which they are a part. Her research focuses on the characteristics that make successful leaders, namely courage, a commitment to excellence, and a willingness to sacrifice. Policy issues are also addressed, stressing the importance of approaches which include government, business, private non-profit organizations, and communities. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Annotation Some of today's best urban leaders don't work for the government -- they can be found in nonprofit organizations that serve the working class and poor populations. Based on interviews conducted in major cities including Atlanta, Chicago, Houston, San Francisco, Washington D.C., and New York, this study focuses on exceptional leaders who have developed effective solutions to the complex problems of our inner cities, including education, economic development, and community safety. The book includes profiles of innovators such as Robert Woodson, founder of the Washington, D.C. based National Center for Neighborhood Enterprise, whose work on affordable housing, gang violence, and black entrepreneurship earned a MacArthur Foundation Fellowship (the "genius" award); MacArthur Fellowship and Heinz Prize winner Bob Moses, founder of the Algebra Project that prepares low-income students for joining today's technology-dominated workforce; Rheedlen Center head Geoff Canada, who received the Heinz Prize for his "anti-violence among youth" work; and Reverend Eugene Rivers, one of the founders of the Ten-Point Coalition that helped to reduce gang violence in Boston. The New Urban Leadership investigates how and why expert problem solvers chose their career paths, what qualities make them especially successful in their work, and the methods they use to train the next generation of urban leaders
1. The legacy of the past -- 2. Kent Amos -- 3. Robert Moses -- 4. Eugene Rivers -- 5. Defining moments and other influences -- 6. The internal change strategy -- 7. Promising practices : four case studies -- 8. Looking to the future.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Urban renewal -- United States -- Case studies; Inner cities -- United States -- Case studies; Civic leaders -- United States; Leaders -- États-Unis.; Rénovation urbaine -- États-Unis -- Études de cas; SOCIAL SCIENCE -- Poverty & Homelessness; POLITICAL SCIENCE -- Public Policy -- City Planning & Urban Development; Civic leaders; Inner cities; Urban renewal; United States; Case studies; Case studies; Études de cas